MARKET ORIENTATION’S ROLE IN IMPROVING MARKETING PERFORMANCE THROUGH COMPETITIVE ADVANTAGE (Universitas Dr. Soetomo, 2022)
Marketing performance is an achievement measure gained from entirely marketing activities of the organization. The purpose of this study to analyses the aftereffect of market orientation on marketing performance through competitive advantage. Type of the study is explanatory research. Research samples are 82 palm oil distributors by using total sampling technique. Analysis in this study use Partial Least Square (PLS) analysis. Analysis result proved that Market Orientation has significant effect on competitive advantage however does not affected significant on Marketing performance, while competitive advantage has significant effect on marketing performance.